The Effect of Red Dragon Fruit on Tumor Necrosis Factor-α (TNF- α) Tiggered by Sub-maximal Exercise. Issue 1 (March 2021) - Harahap, N S; Simatupang, N; Suprayitno,
Abstract: Sub-maximal exercise also induces changes in the exercise of pro-inflammatory cytokine cell components such as TNF-α (Tumor Necrosis Factor-α).The purpose of this study was to determine the effect of red dragon fruit administration on changes in pro-inflammatory cytokines Tumor Necrosis Factor-α (TNF-α) after sub-maximal exercise. The research was carried out at the Faculty of Sport Science, State University of Medan. This study used experimental pretest and posttest group design. The research sample was twenty students divided into two groups. Group A: given sub-maximal exercise and placebo; Group B: received sub-maximal exercise and red dragon fruit. Sub-maximal exercise is conducted running on a treadmill with a sub-maximal intensity, a frequency of three times a week, lasting four weeks. The TNF-a examination was initially carried out at the end of the treatment and then evaluated in the laboratory using the ELISA method. The results showed a significant decrease in TNF-α levels after exercise in the sub-maximal exercise group given red dragon fruit compared to the sub-maximal exercise group given a placebo. The statistical results of the unpaired t-test showed that there was a significant effect of red dragon fruit on decreasing TNF-α levels after sub-maximal exercise. The conclusion is that red dragon fruit significant effect on decreasing TNF-α levels triggered by sub-maximal exercise in students.